Synthesis and in vitro Biological Evaluation of 5-Benzylidene Derivatives of 3-(4-Fluorophenyl)-2,4-thiazolidinedione as Potential α-Glucosidase Inhibitors - Tan, Lay Hsien; Wong, Lai Chun; Avupati, Vasudeva Rao (Asian Journal of Chemistry, 2026)
α-Glucosidase is an intestinal membrane-bound enzyme that catalyzes the final step in the digestion of carbohydrates. It cleaves the glycosidic bonds of oligosaccharides to release glucose and its inhibition results in delayed glucose absorption, thereby inhibiting post-prandial hyperglycemia and hyperinsulinemia in patients with type 2 diabetes. Therefore, in view of the biological role of α-glucosidase as an antidiabetic drug target, a series of 5-(substituted)-1,3-thiazolidine-2,4-diones (C1-C6) were designed, synthesized and characterized by FT-IR, 1H NMR, 13C NMR and mass spectral analyses. All the compounds were subjected to in vitro α-glucosidase inhibitory evaluation. Among the compounds tested for α-glucosidase inhibitory activity, compounds C1 and C3 exhibited significant inhibition, with IC50 values of 0.1363 ± 0.00085 µM and 3.63780 ± 0.00005 µM, respectively. Structure-activity relationship (SAR) analysis of the test compounds revealed the positive contribution of the 1,3-thiazolidine-2,4-dione moiety and the phenyl ring substituents at the 5-position of the 1,3-thiazolidine-2,4-dione scaffold towards the observed activity.